PT Pelindo Marine Service: An Alternative Strategy for Maintenance of the Indonesian Navy’s Warships - Sarjito, Aris (Richtmann Publishing, 2020)
The sea defense strategy, and concepts related to maritime strategy, relating to the overall strategy for achieving victory at sea. In securing the sea, the navy is very dependent on the main weapons system, especially warships. The Indonesian Navy in carrying out its duties rests on the strength of the IFWS (Integrated Fleet Weapons System): Warship, Aircraft, Marines, and Base. The four components of the IFWS are always maintained in combat readiness. One of the ship maintenance facilities in Surabaya that has the potential to be able to carry out maintenance of Navy ships is PT Pelindo Marine Service in Surabaya. This research uses descriptive qualitative approach. Logistics management theory and SWOT analysis are used by researchers as an analysis tool. The results of this study are the logistics management of PT PMS has ability to maintain Navy ships to support sea defense. Constraints faced by PT PMS include: (1) High sedimentation; (2) Inlet flow is crowded, narrow and shallow; and (4) Small dock capacity. The strategies developed by PT PMS to overcome obstacles in the maintenance of the navy’s ships: (1) Implement efficiency in HR, methods, budgets, and infrastructure to maximize profits; (2) Cooperation with similar companies; (3) Investing: dredging, increasing the capacity of the dockyard, and firefighting equipment, and damage control (controlling losses) so it does not get worse than expected.